Pengaruh modifikasi pola hidup medis dengan atau tanpa metformin terhadap kadar asymmetrical dimethyl arginine (ADMA) pada penderita obesitas - Sari Harahap; Dharma Lindarto (Majalah Kedokteran Nusantara The Journal Of Medical School, 2012)
Introduction : Obesity, accumulation of excessive adipose tissue, is a risk factor of cardiovascular diseases. Human adipocytesproduce asymmetrical dimethyl arginine (ADMA), an inhibitor nitric oxide synthase which has important role in endotheldysfunction, and express the full enzymatic machinery responsible for ADMA metabolism. Lifestyle modification and metforminhave lowering body weight and ADMA level effects. This study intends to find out whether lifestyle modification with metforminin obese subjects can make the improvement of ADMA level better.Method : A randomized double blind clinical trial held in 12 weeks on 40 obese subjects having lifestyle modification with andwithout metformin. Antropometric parametres and ADMA level were measured before and after intervention.Results : After intervention, there were decreasement in ADMA level, body weight, waist circumfrence and body mass indexin both group. Mean of ADMA, weight, waist circumfrence, and body mass index reduction in metformin versus placebo groupwere .0235 (SD 0.12) ug/l vs 0.03 (SD 0.1) ug/l (P=0.726), 3.88 (SD 1.23) kg vs 2.36 (SD 1.12) kg (P = 0.0001), 6.39 (SD 0.99)cm vs 5.75 (SD 1.71) cm (P = 0.0001), and 1.76 (SD 0.85) kg/m2 vs 1.08 (SD 0.61) kg/m2 (P = 0.0001).Conclusion : In obese subjects, lifestyle modification in 12 weeks could improve some antropometric parametres but extrametformin did not improve the ADMA level significantly.Keywords : obesity; lifestyle modification; metformin; ADMA